Efeito da associação entre laserterapia e farmacoterapia no modelo de inflamação aguda do tendão induzida por colagenase em ratos - Faria, Raquel Santos de (2014)
The tendinopathy are changes in the health of the tendon, usually frequent and difficult to treat (Langberg and Kongs-GAARD, 2008), requiring considerable financial resources for its treatment.The main objective of the tendon healing process is the restoration of mechanical strength, since the injury induces changes in these mechanical properties. For the assessment of these changes, some models are used, including the monotonic traction tests to failure of the tissue that provide important information about the stiffness and elongation, assisting in the understanding of functional aspects in the progression of the lesion, determining the biomechanical aspects of therapies used for tissue repair. OBJECTIVES: Evaluate the low-level laser action (830nm) and its association with pharmacotherapy using diclofenac sodium in tissue repair tendon, analyzing their mechanical behavior and histological aspects.The animals were anesthetized by intraperitoneal injection of ketamine hydrochloride (90mg / kg) and xylazine (10mg / kg). Then the control animals received as vehicle a transcutaneous injection with 100 mL of sterile saline 0.9% NaCl in the posterior region of the right foot, the Achilles tendon. The animals of the other groups received 100 of transcutaneous injection of collagenase (1 mg / ml;. Sigma Chemical Co, Cat C-6885) in the same region of the Achilles tendon. Next, the animals returned to the containment boxes separated into 5 experimental groups with 7 animals per group: - Control group (CTL): 100 μL was injected of sterile saline (0.9%) in Peritendinous region of the Achilles tendon. - Tendonitis Group untreated (NT): 100 μl was injected Collagenase (1 mg / ml) in Peritendinous region of the Achilles tendon. Diclofenac group (DIC): 100 μl was injected of Collagenase (1 mg / ml) in Peritendinous region of the Achilles tendon. Immediately after injury, the anti-inflammatory diclofenac sodium was injected (1 mg / kg IM).From our results we can conclude that tendinitis promotes histological changes leading to biomechanical changes translating into weakening of the tendon tissue. Pharmacologic therapy with diclofenac sodium improves some mechanical properties, reducing the loss of the maximum traction strength, but the histological aspects are far from healthy tendon. Low power laser therapy also improved both the histological appearance as a functional feature translated by the improvement in maximum traction strength. The association between laser and pharmacological therapies changed histological and biomechanical aspects of the tendon, increasing the deformability due to the increase in displacement at the time of breakage.